Prognostic Role of EGFR/p-EGFR in Patients With Nasopharyngeal Carcinoma: A Meta-Analysis - Chen, Xishan; Liang, Renba; Lai, Lin; Chen, Kaihua; Zhu, Xiaodong (Frontiers in Oncology, 2021)
Background The prognostic value of epidermal growth factor receptor (EGFR)/phosphorylated EGFR (p-EGFR) expression in nasopharyngeal carcinoma remains controversial. A meta-analysis was performed to investigate prognostic significance of EGFR/p-EGFR expression in patients with nasopharyngeal carcinoma. Methods Literatures published before November 2020 were systematically searched in relevant databases, including PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), and Wan fang databases. STATA 13 statistical software was used to analyze the pooled hazard ratio (HR) and 95% confidence interval (CI). Heterogeneity of the studies was examined by I2. Sensitivity and subgroup analysis were performed to explore sources of heterogeneity. The potential publication bias was assessed using both Egger’s and Begg’s tests. Results A total of 20 literatures with 1545 patients were included for the meta-analysis. The meta-analysis results suggested that high expression of EGFR was significantly associated with poor overall survival (OS) (HR = 1.70, 95% CI: 1.24–3.15, P = 0.001) and disease-free survival (DFS) (HR = 2.58, 95% CI: 1.87–3.56, P = 0.000). However, it was not significantly associated with progression-free survival (PFS) (HR = 1.85, 95% CI: 0.90–3.82, P = 0.09) and distant metastasis-free survival (DMFS) (HR = 1.39, 95% CI: 0.73–2.67, P = 0.319). The subgroup analysis indicated that patients with EGFR high expression in studies of higher TNM stage (III–IV) ratio had significantly poor OS (HR = 2.27, 95% CI: 1.09–4.73, P = 0.03), but heterogeneity existed in studies (I2 = 95.1%, P = 0.000). Sensitivity analyses revealed that EGFR expression did not significantly affect OS by an individual study solely, indicating there was inherent heterogeneity in OS cohorts. There was no significant heterogeneity among eight studies in the DFS cohorts (I2 = 0%, P = 0.606). There was significant heterogeneity between EGFR expression and DMFS (I2 = 82.8%, P = 0.000). Sub-group analysis in differentiated carcinoma demonstrated a smaller heterogeneity (I2 = 33.2%). In addition, p-EGFR high expression had no significant correlation with OS (HR = 1.00, 95% CI: 0.88–1.14, P = 0.982) and DMFS (HR = 1.21, 95% CI: 0.96–1.52, P = 0.112). The heterogeneity among p-EGFR and OS studies was small (I2 = 21%, P = 0.26). There was no significant heterogeneity in the DMFS cohorts (I2 = 0%, P = 0.497). Conclusion EGFR high-expression was significantly associated with poor OS and DFS, which may serve as a prognostic predictor for nasopharyngeal cancer. Systematic Review Registration [https://www.crd.york.ac.uk/PROSPERO], identifier [number CRD42021258457].